Local Governance Practices in Federal Context: The Case of Gorkha Municipality (Nepalese Journal of Development and Rural Studies, 2018)
This study highlighted on examining/appraising local governence practices of Nepal in federal context. The study was conducted in Gorkha Municipality located in Gorkha district. The respondents/participants were elected representatives and administrative staffs selected purposively. Necessary data/information were collected through institutional survey, KII, FGD and participant observation techniques. The study found poor physical infrastructure facilities of municipal office for offering efficient administrative services. Eventhough, the administrative staffs are newly appointed young generation found active and interactive. They are accountable and accessible to the service receivers and offering effective and quality service delivery. Elected representatives are also found educated having managerial and leadership skills since they were came from the background of social work. In this federal context, devolved power/jurisdictions of local government in general and Gorkha Municipality in particular have so many opportunities for implementing rural development related programs/projects. However, local government still has been facing challenges of physical infrastructure, economic resources and sufficient human resources.